Ceticismo e ambição : um estudo em metaepistemologia - Vieira, Gregory Gaboardi (2021)
This work is about skepticism understood as the thesis that we don't have empirical knowledge of the external world. It is a metaepistemological work on skepticism: it is about knowing that skepticism is false instead of being about whether skepticism is true or false. It will be assumed that skepticism is false and that we can know that it is false. Our main question is this: assuming that we can know that skepticism is false, in order for us to be able to know that, is it necessary that we can know that based on reasons that are acceptable to the skeptic? The answer 'no' for this question had and has influential proponents, such as John Greco, Robert Nozick and Timothy Williamson, but we will argue it is incorrect. We will defend the answer ‘yes’ to our main question, which is a thesis called 'ambition': the thesis that if we can know that skepticism is false, then we can know that skepticism is false based on reasons that are acceptable to the skeptic. We conclude holding that ambition is true and making a suggestion about what makes some authors claim that they deny ambition even though, in practice, they argue against skepticism as if they assumed ambition to be true.